BIOAVAILABILITY ENHANCEMENT FOR POORLY SOLUBLE DRUGS: A REVIEW - Sahoo, Chinmaya Keshari; Reddy, G. Santhoshini; Vojjala, Abhignya; Reddy, Buchanpally Vikram (Innoriginal: International Journal of Sciences, 2018)
Low aqueous solubility is the major problem encountered with formulation development of new chemical entities as well as for the generic development. Drug with poor water solubility cause slow dissolution rates, generally show erratic and incomplete absorption leading to low bioavailability when administered orally. This present review details about the different approaches used for the enhancement of the solubility of poorly water-soluble drugs. The purpose of this article is to describe the techniques of solubilization for the attainment of effective absorption and improved bioavailability. Keywords: Solubility, bioavailability, absorption, solubilization